2017
DOI: 10.2147/dddt.s122249
|View full text |Cite
|
Sign up to set email alerts
|

Spotlight on siponimod and its potential in the treatment of secondary progressive multiple sclerosis: the evidence to date

Abstract: Siponimod (BAF312) is a synthetic molecule belonging to the sphingosine-1-phosphate (S1P) modulator family, which has putative neuroprotective properties and well-characterized immunomodulating effects mediated by sequestration of B and T cells in secondary lymphoid organs. Compared to fingolimod (ie, precursor of the S1P modulators commercially available for the treatment of relapsing–remitting [RR] multiple sclerosis [MS]), siponimod exhibits selective affinity for types 1 and 5 S1P receptor, leading to a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 22 publications
(22 reference statements)
0
24
0
Order By: Relevance
“…Recent progress in clinical trials of ocrelizumab for PP‐MS and siponimod (BA312) for SP‐MS strongly implicate the involvement of the immune component of acquired immunity, such as T cells and B cells.…”
Section: Proposed Pathogenic Mechanism Of Secondary Progressive Msmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent progress in clinical trials of ocrelizumab for PP‐MS and siponimod (BA312) for SP‐MS strongly implicate the involvement of the immune component of acquired immunity, such as T cells and B cells.…”
Section: Proposed Pathogenic Mechanism Of Secondary Progressive Msmentioning
confidence: 99%
“…Although a limited efficacy of immunomodulatory drugs could be interpreted by an active involvement of innate immunity rather than acquired immunity, recent progress in the clinical trials of ocrelizumab for PP‐MS and siponimod (BA312) for SP‐MS strongly implicate the involvement of immune components of acquired immunity, such as T cells and B cells. Furthermore, pathological studies emphasized the presence of ectopic lymphoid follicles, which is strongly associated with SP‐MS .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the lack of efficacy for fingolimod in progressive MS (16), the potential neuroprotective effects due to the blockade of S1P-S1P receptor axis in CNS prompted the development of novel S1P receptor modulators which work as active drugs. The recent phase-3 EXPAND trial demonstrated that oral administration of siponimod (BAF312), which targets S1P1 and S1P5 (17), attenuates the risk of disability progression in SP-MS, with a major effect in those patients with inflammatory disease (18). For this reason the European Medicines Agency recommended BAF312 as first oral treatment for active SP-MS in November 2019 1 .…”
Section: Introductionmentioning
confidence: 99%